Effect of temperature on digestibility, growth performance and nutrient utilization of corn distiller's dried grains with soluble (DDGS) in Common carp juveniles. (19th December 2019) - Révész, Norbert; Kumar, Shivendra; Bogevik, André S.; Fazekas, Gyöngyvér; Jeney, Zsigmond; Hegyi, Árpád; Sándor, Zsuzsanna Jakabné
Abstract: The aim of this trial was to study the digestibility of corn distiller's dried grains with soluble (DDGS) in Common carp juveniles at two water temperatures 20°C and 30°C. DDGS digestibility was determined based on the substitution of 30% of a reference diet by test DDGS. Three hundred and sixty Common carp juveniles (average weight, 40 ± 7 g) were distributed in thermo‐regulated recirculation water system equipped with twelve 1m 3 fibreglass tanks (30 fish per tank), which were allotted to four experimental group in triplicates. Half of the experimental groups were maintained at 20°C, whereas the other half were exposed to 30°C. Juveniles reared under different temperature regimes were fed either of the two diets, with or without DDGS (DDGS diet or reference diet), to evaluate the interaction effect between water temperature and nutrient digestibility of corn DDGS in Common carp. Diet and water temperature interaction was effective in modulating the response of dry matter digestibility of DDGS ingredient, and digestibility was found higher in juveniles reared at 20°C compared with 30°C. Growth, feed efficiency and protein efficiency were higher at 20°C compared with 30°C. Whole body csomposition of Common carp juveniles was found unaffected due to diet and water temperature interaction. Overall, it is concluded that digestibility and growth performance of Common carp is better at 20°C compared with 30°C, and DDGS has high potential for inclusion in diets of Common carp.